2017
DOI: 10.1093/infdis/jix357
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-Specific T-Cell Transfer for Refractory Cytomegalovirus Infection After Haploidentical Stem Cell Transplantation: The Quantitative and Qualitative Immune Recovery for Cytomegalovirus

Abstract: The adoptive transfer of CMV-specific T cells promotes quantitative and functional recovery of CMV-specific T cells to guard against refractory CMV infection after haplo-SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…Adoptive transfer of ex vivo generated CMV‐specific T lymphocytes (CMV‐CTL) has the potential to restore immunity, prevent CMV, and circumvent the need for pharmacologic therapies . The main results of trials of CMV‐CTL therapy for CMV infection in allo‐HSCT recipients published in the last 5 years are described in Table . Overall, these studies showed that CMV‐CTL therapy was safe, not associated with an increase in GVHD and associated with a reduction in the viral burden.…”
Section: Resultsmentioning
confidence: 99%
“…Adoptive transfer of ex vivo generated CMV‐specific T lymphocytes (CMV‐CTL) has the potential to restore immunity, prevent CMV, and circumvent the need for pharmacologic therapies . The main results of trials of CMV‐CTL therapy for CMV infection in allo‐HSCT recipients published in the last 5 years are described in Table . Overall, these studies showed that CMV‐CTL therapy was safe, not associated with an increase in GVHD and associated with a reduction in the viral burden.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, clinical isolates of human CMV differ in their tropism for HC and bone marrow stromal cells (Apperley et al, 1989;Simmons et al, 1990), so that the pathomechanism of impaired hematopoiesis likely differs between virus variants/strains. Cellular immunotherapy based on transfer of CMV-specific CD8 + T cells (Riddell et al, 1992;Walter et al, 1995;Moss and Rickinson, 2005;Feuchtinger et al, 2010;Neuenhahn et al, 2017) is an option to avoid myelosuppressive side effects as well as renal toxicity of antiviral drugs (Maffini et al, 2016) and to prevent CMV disease in those HCT recipients who are infected with drug-resistant CMV variants (Pei et al, 2017;Chemaly et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of engineered virus-specific T cells has increasingly been used to treat life-threatening CMV [65], EBV [66], and ADV infections [67] after stem cell transplantation. The safety and efficacy of broad-spectrum T cells as treatment for ADV, EBV, CMV, and BKPyV infections after stem cell transplantation was published by Papadopoulou et al [68].…”
Section: Therapy With Virus-specific T Cellsmentioning
confidence: 99%